The Acceptability Test and Analysis of The Nutritional Content of Cookies that Substitute Breadfruit Flour (Artocarpus altilis) and Anchovy Flour (Stolephorus sp.) as Snacks for Stunted Toodlers - Della Maulita; Jonni Syah R Purba; Nopriantini Nopriantini (Sport and Nutrition Journal, 2025)
Background: Breadfruit (Artocarpus altilis) is rich in carbohydrates and fiber, while anchovies (Stolephorus sp.) are rich in protein, calcium, and iron. Both of these foods can be processed into cookies as a snack that has the potential to support the growth and development of stunted children. Objective: This study aims to determine the acceptability test and analyze the nutritional content of cookies that substitute breadfruit flour (Artocarpus altilis) and anchovy flour (Stolephorus sp.) as snacks for stunted toddlers. Method: This study used an experimental design with three treatments: F1 (85 gr breadfruit flour: 15 gr anchovy flour), F2 (75 gr breadfruit flour: 15 gr anchovy flour), and F3 (65 gr breadfruit flour: 35 gr anchovy flour). This test went through 2 stages: the organoleptic test for acceptability and the nutrient content test for protein, carbohydrates, calcium, and iron. Results: The study reveals that the most favored cookies have color, aroma, texture, and taste, specifically the F1 formulation (85 grams of breadfruit flour and 15 grams of anchovy flour). The Pontianak State Polytechnic Laboratory conducted a nutritional content test of the preferred formulation, revealing protein (6.67%), carbohydrates (50.10%), calcium (6.20%), and iron (0.18 mg). Conclusion: Cookies with breadfruit flour and anchovy flour substitution affect the acceptability of color and aroma, but there is no effect on the acceptability of texture and taste.